Hubungan Stres Akademik dan Regulasi Emosi dengan Perilaku Emotional Eating pada Siswa SMA - Putri, Vania Dita Kusuma; Anisah, Laelatul (Jurnal Bimbingan dan Konseling Ar-Rahman, 2024)
This research aims to determine whether there is a relationship between academic stress, emotional regulation and emotional eating behavior in students. The subjects of this research were students attending SMA, aged between 16 - 17 years. Data analysis in this research took the form of a validity test using the Pearson's product moment correlation method, a reliability test using the Cronbach's Alpha method and a normality test using the Kolmogrov-Swirnow parametric statistical method using the SPPS program version 16.00. Hypothesis testing using a multiple linear regression analysis model can show that the Adjusted R Square value is 0.404 by providing a simultaneous correlation of 40.4%. Partially test the first hypothesis (t test) academic stress has no significant effect on emotional eating (sig = 0.080 > 0.05) and the calculated t value is 1.783. Meanwhile, partial testing of the second hypothesis (t test) shows that emotional regulation has a significant effect on emotional eating (sig = 0.000 < 0.05) and the calculated t value is 4.034. Furthermore, the third partial hypothesis (f test) is that academic stress, emotional regulation have a significant effect on emotional eating (sig = 0.000 < 0.05) and the calculated f value is 20.968 so it can be concluded that variables X1, X2 have a significant influence. ____________________________________________________________________Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara stres akademik, regulasi emosi dan perilaku emotional eating pada siswa. Subyek penelitian ini adalah siswa yang bersekolah di SMA, yang berusia antara 16 – 17 tahun. Analisis data dalam penelitian ini berupa uji validitas menggunakan metode pearson’s product moment correlation, uji reabiltas menggunakan metode Alpha Cronbach’s dan uji normalitas menggunakan metode statistic parametric kolmogrov-swirnow dengan menggunakan program SPPS versi 16.00. Pengujian hipotesis dengan model analisis regresi linear berganda dapat diketahui nilai Adjusterd R Square sebesar 0,404 dengan memberikan sumbungan secara simultan sebesar 40,4 %. Uji hipotesis pertama secara parsial (uji t) stres akademik tidak berpengaruh terhadap emotional eating dengan signifikan (sig = 0,080 > 0,05) dan nilai t hitung sebesar 1,783. Sementara pengujian hipotesis kedua secara parsial (uji t) regulasi emosi berpengaruh terhadap emotional eating dengan signifikan (sig = 0,000 < 0,05) dan nilai t hitung sebesar 4,034. Selanjutnya hipotesis ketiga secara parsial (uji f) stres akademik, regulasi emosi berpengaruh terhadap emotional eating dengan signifikan (sig = 0,000 < 0,05) dan nilai f hitung sebesar 20,968 sehingga dapat disimpulkan bahwa variabel X1, X2 ada pengaruh yang signifikan.